2022
DOI: 10.3390/jcm11175200
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implant (IDI) Alone and Combined with Navigated 577 nm Subthreshold Micropulse Laser (SML) for Diabetic Macular Oedema

Abstract: Background: The anatomical and functional changes after intravitreal dexamethasone implant (IDI) alone and combined with navigated subthreshold micropulse laser (NSML) in diabetic macular oedema (DMO) were compared. Methods: Patients with a clinically confirmed diagnosis of non-proliferative diabetic retinopathy (NPDR) and DMO were enrolled in this prospective study and were randomly assigned to two different treatment groups: thirty patients were treated with IDI (IDI group), and the other 30 patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In terms of the limitation, the obtained results require confirmation in larger studies with a control group. Toto et al [90] also demonstrated the effect of MPLT in addition to a dexamethasone implant. The combined therapy reduced the frequency and the number of required injections, thus extending the treatment-free interval.…”
Section: Subthreshold Micropulse Laser Treatment and Intravitreal The...mentioning
confidence: 99%
“…In terms of the limitation, the obtained results require confirmation in larger studies with a control group. Toto et al [90] also demonstrated the effect of MPLT in addition to a dexamethasone implant. The combined therapy reduced the frequency and the number of required injections, thus extending the treatment-free interval.…”
Section: Subthreshold Micropulse Laser Treatment and Intravitreal The...mentioning
confidence: 99%